Interstate Fiscal Disparity in State Fiscal Year 1999 - Robert Tannenwald; Nicholas Turner (Federal Reserve Bank of Boston, 2004)
This paper compares states in terms of their relative fiscal capacity, fiscal need, fiscal comfort, and tax effort in state fiscal year 1999 (FY1999). It is the most recent in a series initiated by the U.S. Advisory Commission on Intergovernmental Relations (ACIR) in 1962. As in previous studies, the authors use the representative tax system and representative expenditure system methodologies in their analysis. Compared with FY1997, the authors find less interstate disparity in fiscal capacity, fiscal need, and fiscal comfort. However, such disparity, though diminished, remains substantial. The New England and Mid-Atlantic regions remain the most 'fiscally comfortable', while the East South Central and West South Central regions are still the most 'fiscally stressed'.
Keywords: H71; H72; 330; state and local government taxation; state and local government expenditure; Länderfinanzen; Steueraufkommen; Öffentliche Einnahmen; Schätzung; Index; USA